Association of anatomical characteristics of teats with quarter-level somatic cell count (2017)
ABSTRACT: Mastitis occurs after bacteria successfully traverse the teat orifice and cause an intramammary infection. Anatomical characteristics of the teat are potential risk factors for infection. The objective of this study was to identify potential associations between anatomical characteristics of teats and quarter-level somatic cell count (QSCC) from cows on larger dairy farms in Wisconsin. Teat dimensions (length and diameter at the teat barrel and apex) were measured, and hyperkeratosis scores were assessed for 3,713 quarters of 959 cows on 9 dairy farms. The SCC of quarter milk samples obtained from those teats was determined. Multivariate models were used to determine associations of teat anatomical characteristics with QSCC. Subclinical mastitis was defined as a quarter milk sample with SCC of >150,000 cells/mL. Teat dimensions and milk components varied among farms. In the group of farms enrolled in this study, prevalence of subclinical mastitis in mammary gland quarters ranged from 13.6 to 28.9%. An interaction of teat apex diameter and quarter position (front or rear) was identified for QSCC. For both front and rear quarters, a tendency existed for narrower teat barrels to be associated with increased QSCC. However, for front quarters only, greater diameter of the teat apex was associated with increased QSCC. Teat shape (square or triangular teats) was not associated with QSCC. Milk samples obtained from teats with hyperkeratosis scores of very rough had greater QSCC compared with milk samples obtained from teats with hyperkeratosis scores of normal, smooth ring, or rough ring.